2021
DOI: 10.1159/000521515
|View full text |Cite
|
Sign up to set email alerts
|

Early Insulin Resistance, Type 2 Diabetes, and Treatment Options in Childhood

Abstract: Background T2D (Type 2 Diabetes) represents just the tip of the iceberg of the complex metabolic alterations associated with obesity and other clinical conditions associated to impaired adipose tissue storage. Summary Available data have suggested the presence of a continuous spectrum of metabolic alterations developed in the progression from IR to T2D, most of which are likely preventable through the early characterization of all the multiple risk factors involved. Therefore, the complete characterization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 114 publications
0
16
0
Order By: Relevance
“…Taken together, these results suggest a progressive worsening of insulin sensitivity state ranging from mild to severe DKA state. It is well known that insulin levels during a fasting state and after an oral glucose load differs significantly according to insulin sensitivity, having subjects with insulin resistance (e.g., obese children or subject with lipodystrophies) significantly higher values 17,25 . Similarly, it is well known that values of glucose/insulin ratio in a fasting state significantly and inversely reflects insulin sensitivity 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these results suggest a progressive worsening of insulin sensitivity state ranging from mild to severe DKA state. It is well known that insulin levels during a fasting state and after an oral glucose load differs significantly according to insulin sensitivity, having subjects with insulin resistance (e.g., obese children or subject with lipodystrophies) significantly higher values 17,25 . Similarly, it is well known that values of glucose/insulin ratio in a fasting state significantly and inversely reflects insulin sensitivity 26 .…”
Section: Discussionmentioning
confidence: 99%
“…The increase in BMI-SDS was greater in children aged 2–6 years. In addition, they smartly demonstrated that overweight and obesity presented in 11.2% of those with normal weight in the pre-pandemic period and obesity presented in 21.4% of those with overweight in the pre-pandemic period [ 40 ]. Taken together, these results and further confirming data reported in the very near future will strongly highlight the relevant and global burden of childhood obesity and its related parallel increase of metabolic complications.…”
Section: Epidemiology Of Pediatric Obesity and Its Major Risk Factorsmentioning
confidence: 99%
“…A family history positive for hypertension, CVD, T2DM or gestational diabetes, diagnosis of polycystic ovary syndrome (PCOS), nonalcoholic fatty liver disease (NAFLD) and evidence of acanthosis nigricans and visceral adiposity are other risk factors [44 ▪ ]. Gender influences IR prevalence, in particular girls have demonstrated to be more insulin resistant than boys, although after puberty males are at higher risk than females to develop IR [45].…”
Section: Risk Factors For Insulin Resistancementioning
confidence: 99%